CARP-1 Functional Mimetics: A Novel Class of Small Molecule Inhibitors of Medulloblastoma Cell Growth - Ashour, Abdelkader E.; Jamal, Shazia; Cheryan, Vino T.; Muthu, Magesh; Zoheir, Khairy M. A.; Alafeefy, Ahmed M.; Abd-Allah, Adel R.; Levi, Edi; Tarca, Adi L.; Polin, Lisa A.; Rishi, Arun K. (PLOS ONE, 2013)
Medulloblastomas (MBs) constitute an aggressive class of intracranial pediatric tumors. Current multimodality treatments for MBs include surgery, ionizing radiation, and chemotherapy. Toxic side effects of therapies coupled with high incidence of recurrence and the metastatic spread warrant development of more effective, less toxic therapies for this disease. CARP-1/CCAR1 is a peri-nuclear phospho-protein that is a co-activator of the cell cycle regulatory anaphase promoting complex/cyclosome (APC/C) E3 ligase. CARP-1 functional mimetics (CFMs) are a novel class of small molecule compounds that interfere with CARP-1 binding with APC/C subunit APC-2, and suppress growth of a variety of cancer cells in part by promoting apoptosis. Here we investigated MB growth inhibitory potential of the CFMs and found that CFM-4 inhibits growth of MB cells in part by inducing CARP-1 expression, promoting PARP cleavage, activating pro-apoptotic stress-activated protein kinases (SAPK) p38 and JNK, and apoptosis. Gene-array-based analysis of the CFM-4-treated Daoy MB cells indicated down-regulation of a number of key cell growth and metastasis-promoting genes including cell motility regulating small GTP binding protein p21Rac1, and extracellular matrix metallopeptidase (MMP)-10. Moreover, CFM-4 treatment stimulated expression of a number of molecules such as neurotrophin (NTF)3, and NF-κB signaling inhibitors ABIN1 and 2 proteins. Overexpression of NTF3 resulted in reduced MB cell viability while knock-down of NTF3 interfered with CFM-4-dependent loss of viability. CFMs also attenuated biological properties of the MB cells by blocking their abilities to migrate, form colonies in suspension, and invade through the matrix-coated membranes. Together our data support anti-MB properties of CFM-4, and provide a proof-of-concept basis for further development of CFMs as potential anti-cancer agents for MBs.